Behavior of Symmetric Deg Coindex and its Applications - S. PARAMESWARI; K. BALASANGU (Utilitas Mathematica, 2025)
In QSPR/QSAR investigations, topological indices, which are molecular graph invariants, are utilized to forecast the physicochemical characteristics of chemical compounds. In this research, we present the Symmetric deg coindex, a revolutionary degree-based topological index. Investigations into the topological index’s mathematical features and a study of its link with various physicochemical aspects relating to lithium cluster and octane isomers were also conducted.